Prove ##(a\cdot b)\cdot c =a\cdot (b \cdot c)## using Peano postulates

  • #1
issacnewton
1,026
36
Homework Statement
Prove ##(a\cdot b)\cdot c =a\cdot (b \cdot c)## using Peano postulates given that ##a,b,c \in \mathbb{N}##
Relevant Equations
The book I am using ("The real numbers and real analysis" by Ethan Bloch) defines Peano postulates little differently.

Following is a set of Peano postulates I am using. (Axiom 1.2.1 in Bloch's book)


There exists a set ##\mathbb{N}## with an element ##1 \in \mathbb{N}## and a function ##s: \mathbb{N} \rightarrow \mathbb{N} ## that satisfy the following three properties.

1) There is no ##n \in \mathbb{N}## such that ##s(n) = 1##
2) The function ##s## is injective.
3) Let ##G \subseteq \mathbb{N}## be a set. Suppose that ##1 \in G##, and that if ##g \in G## then ##s(g) \in G##. Then ## G = \mathbb{N} ##

And addition operation is given in Theorem 1.2.5 as follows

There is a unique binary operation ##+: \mathbb{N} \times \mathbb{N} \to \mathbb{N} ## that satisfies the following two properties for all ##n, m \in \mathbb{N} ##

a. ## n + 1 = s(n) ##
b. ## n + s(m) = s(n + m) ##

Multiplication operation is given in Theorem 1.2.6 as follows

There is a unique binary operation ## \cdot: \mathbb{N} \times \mathbb{N} \to \mathbb{N} ## that satisfies the following two properties for all ##n, m \in \mathbb{N} ##

a. ##n \cdot 1 = n ##
b. ## n \cdot s(m) = (n \cdot m) + n ##

I am also going to assume following results for this proof.
Identity law for multiplication for ##a \in \mathbb{N} ##
$$ a \cdot 1 = a = 1 \cdot a $$

Distributive law

$$ c \cdot (a + b) = c \cdot a + c \cdot b $$

=============================================================
with this background, we proceed to the proof. Let us define a set

$$ G = \{ z \in \mathbb{N} | \; x, y \in \mathbb{N}\; (x \cdot y) \cdot z = x \cdot (y \cdot z) \} $$

We want to prove that ##G = \mathbb{N} ##. For this purpose, we will use part 3) of Peano postulates given above. Obviously, ## G \subseteq \mathbb{N} ##. Let ##x, y \in \mathbb{N}## be arbitrary. Using Identity law for multiplication, we have ##(x \cdot y) \cdot 1 = (x \cdot y) ## and ##x \cdot (y \cdot 1) = x \cdot y = (x \cdot y) ##. Since ##1 \in \mathbb{N}## from Peano postulates, it follows that ##1 \in G##. Suppose ## r \in G##. So ##r \in \mathbb{N}## and

$$ \forall x,y \in \mathbb{N} \; \bigl[ (x \cdot y) \cdot r = x \cdot (y \cdot r) \bigr] \cdots\cdots (1) $$

Now, let ##x, y \in \mathbb{N}## be arbitrary. Now, using addition definition part a), ##(x \cdot y) \cdot s(r) = (x \cdot y) \cdot (r+1)##. Now using Distributive law, we have ##(x \cdot y) \cdot s(r) = (x \cdot y) \cdot r + (x \cdot y) \cdot 1##. Since ##r \in G##, we have , from equation (1), that ##(x \cdot y) \cdot r = x \cdot (y \cdot r) ##. So, we have ##(x \cdot y) \cdot s(r) = x \cdot (y \cdot r) + (x \cdot y) \cdot 1##. And using Identity law for multiplication, ##(x \cdot y) \cdot 1 = (x \cdot y)##. It means that ##(x \cdot y) \cdot s(r) = x \cdot (y \cdot r) +(x \cdot y)##. Now, using distributive law, ##(x \cdot y) \cdot s(r) = x \cdot (y \cdot r + y)##. And, using definition of multiplication part b), ##y \cdot r + y = y \cdot s(r)##. So, we have ##(x \cdot y) \cdot s(r) = x \cdot (y \cdot s(r))##. And since ##x, y \in \mathbb{N}## are arbitrary, it proves that

$$ \forall x,y \in \mathbb{N} \; \bigl[ (x \cdot y) \cdot s(r) = x \cdot (y \cdot s(r)) \bigr] $$

Since ##s(r) \in \mathbb{N}##, this proves that ##s(r) \in G##. So, ##r \in G## implies that ## s(r) \in G##. Using part 3) of the Peano postulates, it follows that ## G = \mathbb{N}##.

Now, if ##a,b,c \in \mathbb{N}##, we have ##c \in G## and it follows that ##(a\cdot b)\cdot c =a\cdot (b \cdot c)##.

Is this a valid proof ?

Thanks
 
  • Like
Likes bhobba
Physics news on Phys.org
  • #2
Looks good.
 
  • Like
Likes bhobba and issacnewton

Related to Prove ##(a\cdot b)\cdot c =a\cdot (b \cdot c)## using Peano postulates

What are Peano postulates?

The Peano postulates are a set of axioms for the natural numbers proposed by the Italian mathematician Giuseppe Peano. They include the existence of a first natural number (usually 0 or 1), the existence of a successor function, and properties that ensure the natural numbers are well-ordered and each number has a unique successor.

What is the associative property of multiplication?

The associative property of multiplication states that for any three numbers, the way in which the numbers are grouped when multiplied does not change the product. In mathematical terms, this is expressed as (a·b)·c = a·(b·c).

How can Peano postulates be used to prove the associative property of multiplication?

Peano postulates define the natural numbers and their basic properties, including addition and multiplication. To prove the associative property of multiplication using these postulates, one typically uses induction, starting with the base case and then proving the property holds for the successor of any natural number.

What is mathematical induction and how is it applied in this proof?

Mathematical induction is a method of proof used in mathematics to prove a statement for all natural numbers. It involves two steps: the base case, where the statement is proven for the first natural number, and the inductive step, where one assumes the statement is true for an arbitrary natural number and then proves it for its successor. This method is used to prove the associative property of multiplication by showing it holds for 0 (or 1) and then for any successor number.

Can the associative property of multiplication be proven without using Peano postulates?

Yes, the associative property of multiplication can be proven using other axiomatic systems or algebraic structures such as rings or fields. However, using Peano postulates is a fundamental approach in number theory and foundational mathematics, as it builds the property from the basic axioms defining natural numbers.

Back
Top